The Composition of Fiscal Consolidation Matters : Policy Simulations for Hungary - Guerson, Alejandro (IMF Working Papers; Working Paper, 2013)
This paper evaluates policy alternatives to achieve permanent fiscal consolidation in Hungary, based on a general equilibrium calibration. The main finding is that the composition of the consolidation, as determined by the mix of revenue and expenditure measures, has important implications for growth, employment, investment, and other key macroeconomic variables. A reduction in current expenditures yields the smallest GDP contraction in the short term and can increase output in the long term by stimulating labor participation and private investment. On the other end of the spectrum, a consolidation of government investment and corporate taxes are the most costly, as disincentives for private investment result in protracted declines in GDP that compound over time to GDP losses that are multiple times the initial size of the consolidation.